Human-Computer Integration - Farooq, Umer; Grudin, Jonathan (ACM Interactions, 2016)
The era of human-computer interaction is giving way to the era of human-computer integration—integration in the broad sense of a partnership or symbiotic relationship in which humans and software act with autonomy, giving rise to patterns of behavior that must be considered holistically. Cyborgs or brain-computer interfaces may come later, but integration is already well under way.